Modelling for conflict: the legacy of ballistic research and current extremity in vivo modelling. Issue 2 (28th May 2013) - Eardley, William G P; Watts, S A; Clasper, J C
Abstract : Extremity ballistic injury is unique and the literature intended to guide its management is commonly misinterpreted. In order to care for those injured in conflict and conduct appropriate research, clinicians must be able to identify key in vivo studies, understand their weaknesses and desist the propagation of miscited and misunderstood ballistic dogma. This review provides the only inclusive critical overview of key studies of relevance to military extremity injury. In addition, the non-ballistic studies of limb injury, stabilisation and contamination that will form the basis from which future small animal extremity studies are constructed are presented. With an awareness of the legacy of military wound models and an insight into available generic models of extremity injury and contamination, research teams are well placed to optimise future military extremity injury management.